Weight Cycling as a Risk Factor for Low Muscle Mass and Strength in a Population of Males and Females with Obesity. Issue 7 (23rd June 2019) - Rossi, Andrea P.; Rubele, Sofia; Calugi, Simona; Caliari, Cesare; Pedelini, Francesco; Soave, Fabio; Chignola, Elisa; Vittoria Bazzani, Paola; Mazzali, Gloria; Dalle Grave, Riccardo; Zamboni, Mauro
Abstract : Objective: This study aimed to determine whether multiple weight cycles in adulthood are an independent predictor of lower muscle mass and reduced strength, with potential implication for sarcopenia in adults with obesity. Methods: A total of 60 males and 147 females with obesity were included, with a mean BMI of 37.9 ± 6.0 kg/m 2 and a mean age of 52.6 ± 12.4 years. Muscle strength was evaluated with handgrip and appendicular skeletal muscle mass was measured with dual‐energy x‐ray absorptiometry. Results: Participants were categorized into the following three groups: non‐weight cyclers, mild weight cyclers, and severe weight cyclers. From a binary logistic regression that considered muscle mass categories as a dependent variable and weight cycling categories, age, and sex as independent variables, severe weight cyclers showed a 3.8‐times increased risk of low muscle mass (95% CI: 1.42‐10.01). Considering handgrip strength categories as a dependent variable and weight cycling categories, age, sex, and BMI as independent variables, severe weight cycling was associated with an increased risk of low muscle mass (about 6.3 times, 95% CI: 1.96‐20.59). Severe weight cyclers showed a 5.2‐times greater risk of developing sarcopenia. Conclusions: In adults with obesity, weight cycling is associated with lower muscle mass and strength and a greater likelihood of developing sarcopenic obesity.